Exposure to air pollution and scarlet fever resurgence in China: a six-year surveillance study - Yonghong Liu (Nature Portfolio, 2020)
The reason for a re-emergence of scarlet fever in China remains unclear. Here the authors show that the number of scarlet fever cases surged in 2011 peaking in 2018, this correlates with an increase in NO2 and O3 but does not necessarily imply causation.